Trust, trustworthiness and justice perception toward the head of department - Chua, Bee Seok; Tan, Cho Chiew (2013)
Trust in the employer is one of the important elements for organizations to develop and maintain. This study aimed to investigate what makes individual employee trust the organizations they work for and tested the relationships of trust, perceived organizational trustworthiness, and justice perception with employees’ trust in their employing organization. This study also aimed to examine the moderating effect of trustworthiness in the relationship between justice perception and trust. A total of 163 employees from two of the Malaysia’s government department participated in the present study. The trustworthiness facets were measured by using the scale developed by Mayer and David (1999). Perceptions of procedural justice, distributive justice, interpersonal justice and information justice were measured using the scale developed by Colquitt (2001). Trust was assessed using the five-item that developed by Mayer and Gavin (2005). The results showed that all the sub scales of trustworthiness and justice perception were significant predictor of trust. Justice and trustworthiness were also found to interact such that justice forms a stronger predictor of trust in organizations when trustworthiness is highly developed. The implications of these findings for research are discussed.